The Effect of Application of Goat Stage And TSP Fertilizer on The Growth and Production of (Chrysantemum morifolium R.) - Novita sari Novita sari; Ni Komang Alit Astiari; I Gusti Made Arjana (SEAS (Sustainable Environment Agricultural Science), 2023)
The purpose of this study was to determine the effect of goat fertilizer and TSP fertilizer on the growth and yield of chrysanthemum (Chrysantenum morifolium R.), conducted at the green house of Pudak Lestari Agrotourism, Pancasari Village, Sukasada District, Buleleng Regency, Bali, from May to in August 2022. This study used a Randomized Block Design (RBD) consisting of 2 factors arranged factorially. The first factor tested was goat manure (K), which consisted of 4 dose levels, namely: K0 = 0 tons/ha, K1 = 15 tons/ha, K2 = 30 tons/ha, K3 = 45 tons/ha while the second factor was TSP (T) fertilizer consisting of 4 dose levels, namely: T0 = 0 kg/ha, T1 = 175 kg/ha, T2 = 350 kg/ha, T3 = 525 kg/ha, each of which was repeated 3 times so that there are 48 trial plots. The research results showed that the interaction between goat manure and TSP fertilizer had no significant effect on all observed variables. Treatment of goat manure had a significant effect only on leaf area, flower diameter, long weight of flower stalks, fresh weight of economic flowers and other variables had no significant effect. The highest economic fresh weight of flowers was obtained from goat manure at a dose of 45 tons ha-1, namely 48.25 g, an increase of 23.97% when compared to no goat manure, namely 38.92 g. The TSP fertilizer treatment obtained the highest plant height and flower diameter in the TSP fertilizer treatment at a dose of 525 kg ha-1, namely 12.67 cm and 10.18 cm compared to that without TSP fertilizer application, namely 10.71 cm and 9.40 cm.